Association between Sleep Quality and Cardiac Autonomic Modulation in Adolescents: A Cross Sectional Study - de Lima Lins-Filho, Ozeas; Andrade-Lima, Aluisio; Torres, Auguste Daniel; Oliveira, Luciano Machado; do-Prado, Wagner Luiz; Ritti-Dias, Raphael; Christofaro, Diego Giulliano Destro [UNESP]; Farah, Breno Quintella (Thieme, 2023)
Objective To analyze the impact of sleep quality/duration on cardiac autonomic modulation on physically active adolescents with obesity. Materials and Methods The present cross-sectional study included 1, 150 boys with a mean age of 16.6 ± 1.2 years. The assessment of cardiac functions included the frequency domain of heart rate variability (HRV; low frequency - LF; high frequency - HF; and the ratio between these bands -LF/HF -, defined as the sympathovagal balance), and each parameter was categorized as low/high. Physical activity levels and sleep quality/duration were obtained by questionnaires. Abdominal obesity was assessed and defined as waist circumference > 80th percentile. Results Poor sleep quality resulted in lower HF (odds ratio [OR]: 1.8; 95% confidence interval [95%CI]: 1.01-3.21]) regardless of physical activity and abdominal obesity. Moreover, the study found no association between sleep duration and HRV parameters in adolescents. Conclusion Sleep quality, not sleep duration, reduces parasympathetic cardiac modulation apart from other factors such as physical activity and abdominal obesity in adolescents.
Keywords: adolescent; autonomic nervous system; cardiovascular system; exercise; sleep